The epidemiology of recurrent abdominal pain from 2 to 6 years of age: Results of a large, population-based study - Ramchandani, P; Hotopf, M; Sandhu, B; Stein, A; Team, ALSPACS (2005)
Objective. Recurrent abdominal pain (RAP) is one of the most common complaints of childhood and is associated with several adverse outcomes in adulthood. Few large, population-based, longitudinal studies have been conducted. The purpose of this study was to investigate the prevalence and epidemiologic features of RAP through early childhood. Design. We report findings from a large, population-based, cohort study of childhood (the Avon Longitudinal Study of Parents And Children). The prevalence and continuity of RAP from 2 to 6 years of age were explored, with associated physical and psychological symptoms among the children and their parents. Results. In a population cohort of 13 971 children, RAP was reported for 11.8% of 6-year-old children. It was less common at ages 2 years (3.8%) and 3 years (6.9%). There was a striking degree of continuity of RAP between the ages of 2 and 6 years. RAP was associated with headaches and limb pains among children and with higher rates of anxiety among both children (adjusted odds ratio: 2.12; 95% confidence interval: 1.70-2.65) and their mothers (odds ratio: 1.75; 95% confidence interval: 1.30-2.36). Conclusions. In a large, population-based, cohort study, RAP was found to be increasingly common up to the age of 6 years. Children with RAP at a young age have a high risk of RAP later in childhood. RAP is associated with other somatic pain symptoms among children and with symptoms of anxiety among children and their mothers. These findings highlight the high prevalence and continuity of RAP through early childhood and the importance of considering psychological symptoms for these children and their families. Copyright © 2005 by the American Academy of Pediatrics.